RECTIFYING THE TEACHING OF INTENSIVE READING THROUGH METACOGNITIVE STRATEGY: A CASE IN AN INDONESIAN JUNIOR HIGH SCHOOL - Rinia Zatalini (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2019)
Since intensive reading has long been a part of curriculum core in Indonesia and is the main and only English skill tested in the National Examination, many teaching procedures usually focus on ways to assist students succeed in the examination. Therefore, there is a tendency for teachers to simply equip students with texts and help to make sense of the texts by translation so that enabling students to answer the given questions. While it may be helpful to some extent, there is a claim that this mode of teaching is (1) less accurate as it is deemed as practising reading, not teaching students how to read and (2) less effective for a mere texts’ translation affords insufficient support for profound understanding and autonomy in learning to occur. This paper thus addresses this teaching issue happened specifically in a junior high school in Indonesia, where teachers still use translation, i.e. Grammar Translation Method, in teaching reading with a lot of practices and less strategy of how to read. Theoretical foundations of intensive reading and theories of language learning are critically discussed, which then lead to suggest the metacognitive strategy as a potential solution to resolve the issue. This paper hence could (a) enhance our understanding on intensive reading and its relation to language learning theories and (b) offer an insight of possible solution to cope other cases similar to the one presented in this paper.